Technology Factors, ERP System and Organization Performance in Developing Countries - Ibrahim Mohammed Egdair; M Farizal Rajemi; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2015)
This aims to explore a set of technological factors among the factors for ERP adoption by organizations in developing countries, especially in the context of Libya. The conceptual framework, and the factors and relationships proposed in the review process confirm the impact of the proposed framework. The discussion of certain factors with reference to particular countries have some common characteristics that unite their comparison in terms of the government sector. There are many similarities between the cultural, structural and technological factors considered. It is important to integrated these factors to determine their importance in a comprehensive study. This provides knowledge of their impact on ERP adoption and organizational performance, because it is considered a starting point for further studies in the Middle East and North Africa, especially in the context of Libya. Keywords - ERP system, organization performance, Technology factors, developing countries, Libya